2004
DOI: 10.1162/1054746041422334
|View full text |Cite
|
Sign up to set email alerts
|

Using Augmented Virtuality for Remote Collaboration

Abstract: This paper describes the concept, prototypical implementation, and usability evaluation of the Augmented Virtuality (AV)-based videoconferencing (VC) system cAR/PE!. We present a solution that allows three participants at different locations to communicate over a network in an environment simulating a traditional face-to-face meeting. Integrated into the AV environment are live video streams of the participants spatially arranged around a virtual table, a large virtual presentation screen for 2D display and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 7 publications
0
36
0
1
Order By: Relevance
“…The AR example (Wang et al 2005) shown in Figure 2 actually corresponds to the node "a" (RV) in the Figure 3 because a virtual mechanical design is inserted into the designers' common real working/viewing environment. The AV example (Regenbrecht et al 2004) in Figure 2, actually fits to the case of node "b" + "e" (VR+VV) on the same level, but under the same previous mega-space because there are two types of subspaces inserted into the base environment "d": real video image of remote collaborators for node "b" (VR) and virtual car product design for node "e" (VV). Two segmented spaces in two independent/individual mega-spaces could also metaphorically augment with each other although they are not structurally located along one path in the recursive hierarchical MA construction.…”
Section: Hierarchical Treementioning
confidence: 82%
See 1 more Smart Citation
“…The AR example (Wang et al 2005) shown in Figure 2 actually corresponds to the node "a" (RV) in the Figure 3 because a virtual mechanical design is inserted into the designers' common real working/viewing environment. The AV example (Regenbrecht et al 2004) in Figure 2, actually fits to the case of node "b" + "e" (VR+VV) on the same level, but under the same previous mega-space because there are two types of subspaces inserted into the base environment "d": real video image of remote collaborators for node "b" (VR) and virtual car product design for node "e" (VV). Two segmented spaces in two independent/individual mega-spaces could also metaphorically augment with each other although they are not structurally located along one path in the recursive hierarchical MA construction.…”
Section: Hierarchical Treementioning
confidence: 82%
“…This paper presents a systematic framework of exploring Mutual Augmentation and applying this concept to support collaboration, communication, and coordination of architectural design beyond single real/virtual space. Augmented Virtuality system (Regenbrecht et al 2004) The concept of structured MA mega-space also opens up a key direction for future research into collaborative virtual environments (CVEs), AR and AV. This paper seeks to investigate how the concept of Mutual Augmentation could be integrated into the traditional CVEs concepts and development to improve the practice of designing in virtual environments.…”
Section: Introductionmentioning
confidence: 99%
“…Findings, reported by Regenbrecht et al (2004), showed also that 3D sound was an important element of a video conferencing system (cAR/PE!). Authors presented a prototype which comprises live video streams of the participants arranged around a virtual table with spatial sound support.…”
Section: Introductionmentioning
confidence: 93%
“…Researchers such as Ishii [7] have explored the use of tangible object interfaces for tabletop collaboration, while Streitz et al [8] use natural gesture and object based interaction in their i-Land smart space. Regenbrecht et al extend the idea of tangible user interfaces and demonstrates the benefits in novel video conference system [9]. In many interfaces there is a shared projected display visible by all participants; however, collaborative spaces can also support private data viewing.…”
Section: Related Workmentioning
confidence: 99%